Sanitation and Diarrhoeal Disease among Children under Five Years in Ghana - Tetteh, S. (University of Ghana, 2013)
In an ideal situation, over 97 percent of newborn infants can be expected to survive through the first five years of life. Reduction in this survival probability in any society is due to the operation of social, economic, biological, and environmental forces. The aim of this study was to investigate the relationship between sanitation and diarrhoeal diseases among children who are less than five years in Ghana. A sample of 2005 women who had given birth in the last five years preceding the survey was drawn from the women’s file of the 2008 Ghana Demographic and Health Survey. In the survey the women were asked whether or not their children suffered from diarrhoeal disease two weeks preceding the survey. Selected socio-economic characteristics of women, environmental factors, and child characteristics were used in the analyses for this study. Due to data limitation, other sanitation variables could not be included in the survey which might have allowed vigorous analyses of the interaction between sanitation and diarrhoeal diseases. Both bivariate and multivariate statistical techniques were employed in the analysis of the data for the study. The analysis shows that wealth of mother, child stool disposal and age of child were the significant predictors of under-five diarrhoeal disease. Most striking is the finding that toilet facility and source of drinking water were not significant predictors of under-five diarrhoeal disease at the multivariate analyses. The study therefore recommends that, education should be intensified on the potential threats of child stool, and the proper way of disposing of it; deliberate focus by government and other institutions should be directed at providing improved sanitation service delivery to rural and urban slum dwellers; and women should be educated on more hygienic way to handle complementary feeding of their children.
Thesis (MA)-University of Ghana, 2013